Regioselective 2′‐Silylation of Purine Ribonucleosides for Phosphoramidite RNA Synthesis. Issue 1 (6th January 2023) - Gaffney, Barbara L.; Jones, Roger A.
Abstract: This article describes high‐yield procedures for protection of purine ribonucleosides based on a reaction that allows highly regioselective 2′‐silylation. Each protocol makes use of two transient protection steps. In the case of tritylation of the 5′ hydroxyl, the 2′, 3′‐diol is protected by reaction with N, N ‐dimethylformamide dimethylacetal (Zemlicka, 1963) to prevent the small, but potentially troublesome, tritylation of the 2′‐hydroxyl that otherwise accompanies tritylation of the 5′‐hydroxyl (Zhang et al., 1997). The phenoxyacetylation of the amino group is carried out after transient hydroxyl and guanine O 6 protection with trimethylchlorosilane using the hydroxybenzotriazole active ester of phenoxyacetic acid. These protocols give overall yields that are three times the best yields available by conventional procedures for adenosine and guanosine, but offer no advantage for cytidine or uridine. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of 5′‐ O ‐(4, 4′‐dimethoxytrityl)‐2′‐ O ‐ tert ‐butyldimethylsilyl‐6‐ N ‐acyladenosine Basic Protocol 2 : Synthesis of 5′‐ O ‐(4, 4′‐dimethoxytrityl)‐2′‐ O ‐ tert ‐butyldimethysilyl‐2‐ N ‐acylguanosine